An experimental study of permeability determination in the lab - Lock, E.; Ghasemi, M.; Mostofi, Masood; Rasouli, V. (2012)
Understanding the flow characteristics in laminar and turbulent flow regime is important for different aspects of reservoir and production engineering. One of the most important parameters in fluid flow is the permeability of the porous media. It is common practice in the industry to use Darcy and Forchheimers equations for characterising the fluid flow in the porous media at laminar and turbulent regimes, respectively. Core flooding experiments were performed with 1.5-inch diameter size core samples from limestone and sandstone formations. The permeability of the samples was measured in the laminar regime at basis flow rate. Then, the flow rate was increased in different steps and permeability was measured, accordingly. The plot of permeability versus flow rate was used to track the evolution of the flow regimes in the core porous media. There are different challenges to monitor the transition between laminar and turbulent regime through core flooding experiments. These challenges are discussed in this paper through both literature review and also experimental results. The results indicated that the core sample preparation, experiment control parameters and also test profiles are important aspects when measuring permeability in the lab. © 2012 WIT Press.